(untitled) (Transport systems and technologies, 2019)
In the article, the offered method of definition of invariant characteristic (deflection) of the combined springs under the influence of external loadings for a research of power characteristic in the vertical direction is for the first time presented and described. The method is based on the use of hardware-software providing SolidWorks (Dassault Systèmes) with the use of Nonlinear Dynamic Analisis and calculation in the environment of MathСAD 15 with creation of the resultant chart of movement. The results of studies of the influence of elements of the improved spring suspension design on its power characteristic are presented for the first time. At a research of power characteristic of advanced construction of spring suspension using a method of definition of invariant characteristic of the combined springs under the influence of external loadingsthe following results are achieved: the elements of the studied model of spring suspension of the cart of the gondola car is designed; movements in separate nodes of elements taking into account actual loads are calculated and defined; charts of movements are created and the efficiency of application of the studied structural elements is estimated. The expediency and efficiency of use of a method of definition of invariant characteristic (deflection) of springs of different constructive models and their power characteristic in spring suspension of carts of freight cars is confirmed at the research, studying and design of modern perspective constructions of a system of vibration damping.